Data-based ethical decision making, lateral relations, and organizational commitment: Building positive workplace connections through ethical operations. Issue 6 (12th July 2018) - Valentine, Sean Robert; Hollingworth, David; Schultz, Patrick
Abstract : Purpose: Focusing on ethical issues when making organizational decisions should encourage a variety of positive outcomes for companies and their employees. The purpose of this paper is to determine the degree to which data-based ethical decision making, lateral relations and organizational commitment are interrelated in organizations. Design/methodology/approach: Data were collected from business professionals employed at multiple locations of a financial services firm operating in the USA. Mediation analysis (based on structural equation modeling) was used to test the proposed relationships. Findings: Results indicated that employees' perceptions of data-based ethical decision making were positively related to perceived lateral relations, and that perceived lateral relations were positively related to organizational commitment. Research limitations/implications: Given that information was collected using only a self-report questionnaire, common method bias could be an issue. In addition, the study's cross-sectional design limits conclusions about causality. Another limitation involves the study's homogenous sample, which decreases the generalizability of the findings. Finally, variable responses could have been impacted by individual frames of reference and other perceptual differences. Practical implications: Results suggest that information flow enhancements should support or be consistent with horizontal information flow enhancements, and that together these factors should increase employee commitment. Originality/value: Given the dearth of existing research, this interdisciplinary investigation is important because it fills gaps in the management literature. This study is also important because the results could inform decisions regarding the use of data analysis in ethical decisions and lateral forms of organizational structuring to improve work attitudes.